Goodwill Amortization in the Italian Civil Code: Estimation Problems and a Methodological Proposal - Baldissera, Annalisa (European Scientific Journal, ESJ, 2022)
In regulating the financial statements, the amortization of goodwill represents a complex problem that requires a careful assessment of the economic conditions of the firm and their foreseeable evolution. This study aims to analyze the topic with specific regard to the Italian context, in order to identify the parameters useful for guiding the amortization processes, in compliance with the limits set by the legislation on financial statements. To this end, the study used a methodology based on the legal-economic analysis of the evolution of Italian legislation from 1882 to today and its effects on the economic valuations implied by amortization. The results show that the accounting for goodwill has changed over time, being characterized in the first phase by the prevalence of conservative accounting and by the consequent need to amortize goodwill in the shortest possible time. Subsequently, the accrual basis prevailed over conservatism, and today the basic rule is represented by the useful life of goodwill. The originality of this study lies in the multidisciplinary approach which, by combining the economic interpretation of the company with the legal rules on reporting, proposes an analysis model applicable in the practice of companies that prepare their financial statements according to the Civil Code.